Evaluation study of the factors of damage to the mosaics preserved in the new musée of Cherchel - mediene, Norelhouda; Ben zghadi, mohammed (The Algerian Historical Journal, 2026)
Ancient civilizations were interested in many arts most notabli the art of mosaic and it was the technique in an-cient period that used to decorating of buil-dings,palaces and baths. This cultural heritage suffers from many factors of damage however its importance specially in mu-seums such as mechanic damage as pression and vi-brations, in addition physi-chemical damage as humi-dity, the heat and salts, and we don t forget biological damage like microorganisms,algae and bird dropping all this types of damage can causes many damage as-pects that distrotion beautiful image of moasaic ,and maybe can lose its historical and artistic value ,soi t is necessary to provide all means of protection and res-toration with conservation to preserve this important cultural heritage